If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 * 5 = 15 Multiply -3 * 5 5x + -15 = 15 Reorder the terms: -15 + 5x = 15 Solving -15 + 5x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 5x = 15 + 15 Combine like terms: -15 + 15 = 0 0 + 5x = 15 + 15 5x = 15 + 15 Combine like terms: 15 + 15 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 9x-40=7x-37 | | (x+14)+3x=180 | | 19-3n=13 | | -37+6x=19+2x | | 3p+5q=7 | | 6+5g=3g+20 | | 4x-10=7x-9 | | 10=0.83(n+6) | | 2-(-2)s=6 | | -x-18=36 | | 0.5x+.01x+12+1x-5=9.96 | | 3d+4(-3)=11 | | 2661=63+63(n-1) | | x^2-kx+9=y | | 4x+3a=bx+2.5a-5 | | 5(x+3)-2=2x+9 | | 6x+8x-42=84-7x | | v-7.5=3.4 | | x^2+9x=15 | | 3r+1=r+8 | | 5r+7=-13+7r | | 9d+4(-7)=15 | | -7+4(1-5x)=x+39 | | y+6.4=9.66 | | X+50=76 | | 63=9(z-92) | | 7v=-10 | | 30x=-140 | | 27x+8=-170 | | -29+2x=-6x+27 | | (8*x^3-24*x^2+10)=0 | | 3+2y=x |